2023
DOI: 10.3390/jpm13060971
|View full text |Cite
|
Sign up to set email alerts
|

Promising Markers of Inflammatory and Gut Dysbiosis in Patients with Post-COVID-19 Syndrome

Abstract: Post-COVID-19 syndrome is a complex of different symptoms, which results in a multisystemic impairment after the suffering from COVID-19 infection. The aim of the study was to reveal the clinical, laboratory, and gut disorders in patients with post-COVID-19 syndrome (n = 39) before and after taking part in the 14-day complex program of rehabilitation. A complete blood count, coagulation test, blood chemistry, biomarkers, and metabolites in serum samples, and gut dysbiosis were revealed in patients on the day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…In a 2018 study, the median reference concentration of PhPA and p-HPhLA obtained using GC-MS in serum samples of 40 healthy volunteers was 0.5 µmol/L [4]. In a recent study, the data also obtained using GC-MS on the same 48 healthy volunteers as in our study (Table 3) demonstrated the presence of PhPA, PhLA, p-HPhAA, and p-HPhLA in serum samples with different frequencies [6]. Only p-HPhLA was measured in all 48 samples.…”
Section: Analysis Of Serum Samples Of the Healthy Volunteerssupporting
confidence: 64%
See 2 more Smart Citations
“…In a 2018 study, the median reference concentration of PhPA and p-HPhLA obtained using GC-MS in serum samples of 40 healthy volunteers was 0.5 µmol/L [4]. In a recent study, the data also obtained using GC-MS on the same 48 healthy volunteers as in our study (Table 3) demonstrated the presence of PhPA, PhLA, p-HPhAA, and p-HPhLA in serum samples with different frequencies [6]. Only p-HPhLA was measured in all 48 samples.…”
Section: Analysis Of Serum Samples Of the Healthy Volunteerssupporting
confidence: 64%
“…We have previously demonstrated that a number of metabolites of aromatic α-amino acids are ubiquitous, and their low serum concentrations reflect the integration of the human metabolism with its microbiota [4]. Some of the metabolites can be used as prognostic markers of infectious complications and outcomes in severe patients with various pathologies [5] and in patients with post-COVID-19 syndrome [6]. These metabolites include phenyl-containing microbial and endogenous derivatives of phenylalanine (phenyllactic (PhLA) and phenylpropionic (PhPA) acids) and tyrosine (4-hydroxyphenyllactic (p-HPhLA), 4-hydroxyphenylacetic (p-HPhAA), 4-hydroxybenzoic (p-HBA), and 4-hydroxyphenylpropionic (p-HPhPA) acids).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a hypoxic state, there is a burden of glucose production (gluconeogenesis) and urea elimination (the urea cycle) in the liver. A recently published study of 39 post-COVID-19 patients in rehabilitation also found high levels of succinic and fumaric acids (TCA cycle metabolites) and associated these observations with hypoxia and inflammation [44]. Although analyzing drug metabolites was out of this study's scope, a notable fact is that corticosteroids, especially dexamethasone, were used for the treatment of severe COVID-19, and corticosteroids increase hepatic gluconeogenesis, reduce peripheral use of glucose, and increase insulin levels, contributing to hyperglycemia in patients.…”
Section: Energy Metabolism Disturbancesmentioning
confidence: 90%
“…Significant alteration in gut microbiota composition is often observed in diseased patients. Such dysbiosis is even described as a potential microbial biomarker for precision medicine [15][16][17]. Indigestible food remains in the colon could be a potential substrate for gut microbes.…”
Section: Introductionmentioning
confidence: 99%